PERHITUNGAN DIMENSI SEAWALL MENGGUNAKAN LAZARUS - Fera Lestari; Randy Setiawan; Dian Pratiwi (Universitas Bandar Lampung, 2018)
PT. Daya Radar Utama has built and repaired various types of ships including steel, aluminum alloy, and fiberglass reinforced plastic. In general, Graving Dock and Noahtu Port Bandar Lampung provide supporting facilities for repairs of large capacity ships (maximum 30000 DWT), Complete facilities and infrastructure for progress in the field of sea transportation. A wave barrier is needed to support the activities in Graving Dock and the Port of Noahtu Bandar Lampung in the form of seawall. Seawall or beach walls are beach buildings that are built on the coastline or on land that are used to protect the beach directly from wave attacks. The location of this study was carried out in the city of Bandar Lampung with research objects, namely on the pier and PT. Daya Radar Utama. Data collection in this study consisted of wind data, wave data, tide data, soil data, and sediment data. These data are obtained from the planning data of the dock construction in the company PT. Daya Radar Utama.To make it easier to get the dimensions of the seawall, a tool is needed to simplify the calculation. One program that can be used to simplify calculating the dimensions needed in a seawall plan is Lazarus because it is open source and discusses relatively easy programming.Calculation of seawall dimensions with this program can be done easily and quickly, compared to manual calculations. In the planning of making seawall stone types affect the seawall. In making seawall using the program, it is necessary to pay attention to rounding for the weight of protected layers.